(untitled) (Journal of Training and Development, 2020)
The dominant category of the labour forces of Nepal are the workers from the informal sectors where basically informal skills learning occurs during the work. However, informal skills learning is not only limited to informal sector jobs. It can take place in all types of organizations, enterprises, and institutions of both formal and informal sectors. It is estimated that more than eighty percent of workers in Nepal acquire their occupational skills during their work. However, it is not evident what are the typologies of working places of those informal skills learners. Taking a qualitative approach of inquiry, this paper analyses the existing legal frameworks and literature from domestic cultural practices. Based on this analysis, it presents a typology of informal skills learning places in Nepal developed mainly considering the points prescribed by Bailey (1994). It is claimed that the typology provides a sound conceptual basis for the identification of main categories and sub-categories of informal skills learning places in Nepal.